(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research is entitled (Relationship between Illustration and Graphic Printing in the Art Works of Kurdistan Regional Artists), The first section includes topics related to the general framework of the study, which consists of: research problem, research importance, research objectives, research limitations and definition of terms. The research problem is identified through several questions as follows: 1- Have the arts of illustration and graphic printing been able to continue according to history and changes in human life and have always been renewed? 2- To what extent has the art of illustration and graphic printing become a subject of work for artists in the Kurdistan region?" 3- To what extent has the art of illustration and graphic printing served as a means of communication and expression in the essence of human culture and history? With the aim of providing an interpretive analysis of illustration art and graphic printing in the Kurdistan region, the second section, which is the theoretical framework of the research, delves into the history of the emergence and development of graphic printing and illustration art. It also discusses the techniques and fields of illustration art and graphic printing. In the third section, researchers have presented examples of artworks created by artists from the Kurdistan region who have worked in the fields of illustration and graphic printing in a scientific manner. The fourth section presents the results, conclusions, recommendations, and references.